Determinação voltamétrica de fibratos em formulações farmacêuticas utilizando eletrodos de carbono vítreo modificados com nanotubos de carbono - Quintero, Jorge Armando Ardila (2012)
In this work voltammetric methods were developed from gemfibrozil (GEM) and bezafibrate (BZF) determination in pharmaceutical formulations for using modified glassy carbon electrode with dihexadecyl hydrogen phosphate containing carbon nanotubes treated chemically. Firstly was studied the voltammetric behavior of GEM in 0.1 mol L 1 (pH 2.0) phosphate buffer solution, was observed an irreversible oxidation peak in 1.31 V. Square-wave adsorptive stripping voltammetry was selected for GEM quantification in pharmaceuticals formulations, with the following parameters: adsorption time of 300 s, frequency of 40 Hz, a pulse amplitude of 45 mV and scan increment of 4 mV. The analytical curve was linear over the concentration range of 7.5 × 10−8 a 1.0 × 10−6 mol L−1 of GEM, represented by following ΔI (μA) = 0,086 + 1,05 × 107 [GEM] (mol L 1), correlation coefficient of 0.997 and detection limit of 5.3 × 10−8 mol L−1. The procedure developed was successfully applied to determine GEM in commercial pharmaceutical samples and the results were compared with the reference method, described in British pharmacopoeia. There was no significant difference (5 %) between the results obtained at a confidence level of 95%. The BZF determination was carried in 0.1 mol L 1 (pH 2.0) phosphate buffer solution and an irreversible peak in 1.09 V was observed. Square-wave adsorptive stripping voltammetry technique was selected for BZF determination with the following parameters: adsorption time of 180 s, frequency of 20 Hz, pulse amplitude of 40 mV and scan increment of 7 mV. The proposed method presented a linear interval between 5.0 × 10−8 a 9.1 × 10−7 mol L−1 and detection limited of 1.6 × 10−8 mol L−1. The BZF was quantified in commercials samples and the results were compared with de spectrophotometric method, with errors between 2.9 e 0.5 %. Finally for each analyte were calculated the number of electrons involved in the oxidation reaction and was proposed a possible mechanism for the oxidation reaction of these drugs, because there are no reports in the literature.